1999
DOI: 10.1111/j.1095-8649.1999.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Male mate preference and size‐assortative pairing in the convict cichlid

Abstract: Male convict cichlids Cichlasoma nigrofasciatum presented three females simultaneously were found to prefer larger females, even if a female's size exceeded their own. This indicates that some mechanism other than male choice, such as female choice or intrasexual competition, must contribute to male-larger assortative pairing in convict cichlids. Despite a preference for larger females, males continued to consort with smaller females when available, and a female's attractiveness was a function of her size rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
26
1
Order By: Relevance
“…For example, Basolo (2004) found that large males of the poeciliid fish Brachyrhaphis rhabdophora preferred large females, and small males preferred small females. Other studies have also found positive assortative mating for body size (Beeching & Hopp 1999;Ros et al 2003;Dosen & Montgomerie 2004). Our results, however, show negative assortative mating for body size in female B. splendens; small females preferred the large male stimulus, while large females preferred the small male stimulus.…”
Section: Discussioncontrasting
confidence: 48%
“…For example, Basolo (2004) found that large males of the poeciliid fish Brachyrhaphis rhabdophora preferred large females, and small males preferred small females. Other studies have also found positive assortative mating for body size (Beeching & Hopp 1999;Ros et al 2003;Dosen & Montgomerie 2004). Our results, however, show negative assortative mating for body size in female B. splendens; small females preferred the large male stimulus, while large females preferred the small male stimulus.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous experiments revealed that males and females of P. taeniatus use body size (an ornamental trait) as well as genetic relatedness (a compatibility criterion) in mate choice, when these criteria were tested independently from each other: as in other cichlids [33][34][35][36][37], both sexes preferred large individuals [32]. Mating with large individuals provides several indirect and direct benefits in biparental cichlids, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sargent et al 1986;Nelson 1995;Howard et al 1998;Beeching and Hopp 1999;Kvarnemo and Forsgren 2000). In addition, mutual mate choice might favour, for example, both highly ornamented males and large females (Kraak and Bakker 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Beeching and Hopp 1999;Bisazza and Pilastro 2000;Suk and Choe 2002). Each test lasted 24 h and was conducted in a tank (730 cm long×47 cm wide tank, water depth 40 cm) divided into five compartments (Fig.…”
Section: Female Preference Testsmentioning
confidence: 99%